Crystal Chemistry and Structural Complexity of the Uranyl Vanadate Minerals and Synthetic Compounds - Ivan V. Kuporev; Sophia A. Kalashnikova; Vladislav V. Gurzhiy (Crystals)
This paper reviews perhaps one of the most enigmatic groups of secondary uranium minerals. The number of uranyl vanadate mineral species does not reach even 20, and they do not display a large range of structural diversity, but those natural phases form rather massive deposits that can be mined as uranium ores. The number of synthetic uranyl vanadates is three times higher than natural phases, and most of them were obtained using hydrothermal and solid-state techniques. Diversity is also evident in their structural parts. The majority of synthetic compounds, both pure inorganic or organically templated, have their structures based upon mineral-like substructural units of francevillite, uranophane, U3O8, and other common topological types, and not even one compound among 57 studied was obtained from simple aqueous solutions at room temperature. This allows us to assume that even under natural conditions, elevated temperatures are required for the formation of isotypic uranyl vanadate minerals, especially in the case of industrially developed thick strata. The structural complexity parameters for natural uranyl vanadates directly depend on the unit cell volume. Keeping in mind that all minerals possess layered structural architecture, it means that structural complexity increases with the increase in the interlayer spacing, which, in turn, depends on the size of cations or water–cationic complexes arranged in the interlayer space. This tendency similarly works for organic molecules, which are incorporated into the uranyl vanadate frameworks. It can also be concluded that the architecture of the uranyl vanadate substructural units defines the complexity of the entire crystal structure.